2016
DOI: 10.1037/spy0000071
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic rewards predict exercise via behavioral intentions for initiators but via habit strength for maintainers.

Abstract: Regular exercise is thought to involve both reflective (e.g., intention) and automatic (e.g., habit) mechanisms. Intrinsic motivation is a reflective factor in exercise initiation; we propose that the experience of intrinsic exercise rewards (enjoyment; stress reduction) may come to function as a factor in exercise automaticity, or habit, and therefore of exercise maintenance. The current studies evaluate whether the relationship between intrinsic exercise rewards and exercise is mediated by behavioral intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 69 publications
1
37
0
1
Order By: Relevance
“…Physical activity enjoyment is often considered an intrinsic motivator for exercise (Phillips et al, 2016). Consistent with Self-Determination Theory (Ryan and Deci, 2000), intrinsic motivation is a key factor for long-term maintenance of exercise behaviors (Ryan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity enjoyment is often considered an intrinsic motivator for exercise (Phillips et al, 2016). Consistent with Self-Determination Theory (Ryan and Deci, 2000), intrinsic motivation is a key factor for long-term maintenance of exercise behaviors (Ryan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with hedonic theory (Kahneman et al, 1999), people are more likely to do what they find pleasurable, while avoiding behaviors that they do not enjoy. Thus, greater physical activity enjoyment is posited to result in increased behavioral intentions to exercise, and in turn, sustained engagement in physical activity (Phillips et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that past behavior may be a stronger predictor of habit strength among intrinsically motivated participants, suggesting that enjoyment derived from autonomously motivated PA may strengthen the relationship between past behavior and habit development even more. In line with this, another study investigated intrinsic rewards such as enjoyment and found that intrinsic rewards predict exercise frequency via habit strengths for maintainers (and via behavioral intentions for initiators) (Phillips et al, 2016). Furthermore, Kaushal and Rhodes (2015) investigated the influence of affective judgments about exercise on habit formation in a longitudinal study among new gym members, and reported that affective judgments at baseline were the main predictor of habit development.…”
Section: Introductionmentioning
confidence: 89%
“…Rather, I highlight the importance of internal goals for complex habit formation and maintenance. Phillips, Chamberland, Hekler, Abrams, and Eisenberg (2016) showed that intrinsic rewards (positive reward, such as enjoyment, or negative reward, such as stress reduction) predicted exercise frequency via habit strength for individuals in a maintenance stage of change. Intrinsic goals, or motivation, may therefore be fundamental to physical activity habit (without intrinsic reward, the habit would cease/extinguish).…”
Section: Assumption 3: Habits Are Goal-independentmentioning
confidence: 99%